IBM i5/OS IP networks : dynamic - Bruinsma, Kent; Coon, Jim; Gloe, Christopher; Jongekryg, Brian; Kasperski, John; Wood, Clair; Johng, Yessong (IBM redbooks., 2007)
Over the course of many years, the developers in both the Endicott and Rochester labs have been working very hard adding functions to each release of OS/400 and i5/OS to make the configuration and use of the IBM System i in a TCP/IP network easier and more powerful. If you need to design an IP network that is self-configuring, fault-tolerant, secure, and efficient in its operation, then this IBM Redbooks publication is for you. We start low with the details of IP interface and route implementation on i5/OS. Through the study of these building blocks, we show how to create IP networks that are easier to configure, tolerant of faults, and can perform both inbound and outbound load balancing. i5/OS has always had many built-in Network Security features. These features have been enhanced to include an Intrusion Detection System (IDS). This allows you to be notified of attempts to hack into, disrupt, or deny service to the system. Moving up to the application layer, we demonstrate the dynamic power of IP by having the DHCP server assigning IP addresses and automatically updating the i5/OS Dynamic DNS. Now clients and servers can be added dynamically to the IP network and assigned a name automatically.